2021
DOI: 10.3390/toxics9070148
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Suitability of Melilotus officinalis for Phytoremediation of Soil Contaminated with Petroleum Hydrocarbons (TPH and PAH), Zn, Pb and Cd Based on Toxicological Tests

Abstract: The article presents issues related to the possibility of using toxicological tests as a tool to monitor the progress of soil treatment contaminated with petroleum substances (TPH, PAH), Zn, Pb and Cd in bio-phytoremediation processes. In order to reduce the high content of petroleum pollutants (TPH = 56,371 mg kg−1 dry mass, PAH = 139.3 mg kg−1 dry mass), the technology of stepwise soil treatment was applied, including basic bioremediation and inoculation with biopreparations based of indigenous non-pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…The bioconcentration factor (BCF), and transport factor (TF), which can exclude the heavy metal concentration differences in soil or root of plants [ 54 , 55 ], were used to evaluate the accumulation and transportation characteristics of heavy metals in soil-ornamental plant system, respectively, as shown in Figure 6 .…”
Section: Resultsmentioning
confidence: 99%
“…The bioconcentration factor (BCF), and transport factor (TF), which can exclude the heavy metal concentration differences in soil or root of plants [ 54 , 55 ], were used to evaluate the accumulation and transportation characteristics of heavy metals in soil-ornamental plant system, respectively, as shown in Figure 6 .…”
Section: Resultsmentioning
confidence: 99%
“…In the past three decades, phytoremediation has been widely investigated for the remediation of petroleum pollutants in soils due to its advantages of sustainability and ecological integrity [ 24 , 25 , 26 , 27 ]. The remediation of petroleum-contaminated soils by energy plants could not only solve the problem of land use, but may also prevent pollutants from entering the food chain, providing a new idea for the remediation of contaminated soil [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is significant to point out that two of the metals found in the components of the cuttings and their leachates were Pb and Ba. The same special attention should be paid to the control measures in confinement cells or treated solids that are reused in linings since it has been demonstrated that both metals can cause toxicological effects in living beings (Steliga & Kluk, 2021;Omar & Vilcaez, 2022).…”
Section: Metalsmentioning
confidence: 99%